A Gendered Account of Alcoholics Anonymous' "Singleness of Purpose". Issue 1 (2nd January 2019) - Sanders, Jolene
ABSTRACT: This study adopts a gendered perspective when looking at the tension within Alcoholics Anonymous (AA) over its singleness of purpose. Due to its very success, those with problems "other than alcohol" are attending AA meetings across the country and are challenging the "deep identification" that takes place within this subculture. Women, as it will be described, have historically had dual addictions and other problems in addition to their primary concern of alcohol dependency. Through the analysis of approximately 300 women's stories, documenting their experiences with alcohol use disorder and recovery in AA over the past 60 years, it is illustrated that not only do women have a history of dual addiction to alcohol and other drugs but that due to gender-role ideology, women have kept their own prescription drug abuse hidden thus not to threaten AA's singleness of purpose.